ANALISIS TEKNIS PEMILIHAN LOKASI TPA REGIONAL MAGELANG (KOTA MAGELANG DAN KABUPATEN MAGELANG) - Diharto, . (Semarang State University, 2008)
Make-up of amount of resident of urban with the make-up of garbage volume. Make-up of garbage volume perhaps will weigh against the final process place operational (TPA), at one blow will cut short the age TPA. This research target is to look for the correct location TPA regional serve the Town of Magelang and Regency Magelang. This TPA is hereinafter managed by together between Town and Regency Magelang. Its analysis use the SNI 03-3241-1991 - SK SNI T-11-1991-03. Pursuant to perception/field observation and interview secondly is party handling garbage in the region, chosen two location alternative that is Countryside of Banyuurip and Countryside of Glagahombo of Subdistrict of Tegalrejo of Regency Magelang. Result of chosen analysis location of TPA regional in Countryside Glagahombo.Peningkatan jumlah penduduk perkotaan dibarengi dengan peningkatan volume sampah. Peningkatan volume sampah tentunya akan memberatkan operasional tempat pemrosesan akhir (TPA), sekaligus akan memperpendek usia TPA. Tujuan penelitian ini adalah untuk mencari lokasi TPA regional yang tepat melayani Kota Magelang dan Kabupaten Magelang. TPA ini selanjutnya dikelola secara bersama-sama antara Kota dan Kabupaten Magelang. Analisisnya menggunakan SNI 03-3241-1991 – SK SNI T-11-1991-03. Berdasarkan pengamatan/observasi lapangan dan wawancara dengan kedua pihak yang menangani persampahan di wilayah tersebut, terpilih dua alternatif lokasi yaitu Desa Banyuurip dan Desa Glagahombo Kecamatan Tegalrejo Kabupaten Magelang. Hasil analisis terpilih lokasi TPA regional di Desa Glagahombo.